Ewing's Sarcoma as a Second Malignancy in Long-Term Survivors of Childhood Hematologic Malignancies. (25th July 2016) - Wolpert, Fabian; Grotzer, Michael A.; Niggli, Felix; Zimmermann, Dieter; Rushing, Elisabeth; Bode-Lesniewska, Beata
Abstract : Modern multimodal treatment has significantly increased survival for patients affected by hematologic malignancies, especially in childhood. Following remission, however, the risk of developing a further malignancy is an important issue. The long-term estimated risk of developing a sarcoma as a secondary malignancy is increased severalfold in comparison to the general population. Ewing's sarcoma family encompasses a group of highly aggressive, undifferentiated, intra- and extraosseous, mesenchymal tumors, caused by several types of translocations usually involving the EWSR1 gene. Translocation associated sarcomas, such as Ewing sarcoma, are only rarely encountered as therapy associated secondary tumors. We describe the clinical course and management of three patients from a single institution with Ewing's sarcoma that followed successfully treated lymphoblastic T-cell leukemia or non-Hodgkin lymphoma. The literature on secondary Ewing's sarcoma is summarized and possible pathogenic mechanisms are critically discussed.